(3eNJUQ EbJHGS GdCfhGQ hEdJeGS GdCRgGQ aj CfSGH GdUMGHI QhGI GdBKGQs - (3GdMGaX GHi eMeO YHO Gddg Hf YHO GdQMef Hf YHO Gddg GdCROi GdETHjdis; (3YHO Gddg Hf Ydj Hf YHO Gddg GddNej GdCfOdSj, CHh eMeO , GdQTGWj,J (B542 (3g` s
(3ChdgG (B:s
(3GdHGHdJi (B: (3HGHdJ ehVY HGdQi , hgh jMji Hf YHO Gddg GdVMGc GdMQGfi GdHGHdJi s
(3BNQgG (B:s
(3Gddjfi (B: (3bQjI Gddjf CMSHgG HeQh hHg ced GdSaQ GdChd s
(3ddQTGWi YHO Gddg Hf Ydi Hf YHO Gddg GddNei GdeJhai SfI (B466(3g`s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B105 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B262s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B133 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B134s
Keywords: (3GdJGQjNs